Stability of High Concentration Capsaicin in Transfersome Carriers in Gel Dosage Form - Novi Lestari; Iskandarsyah; Ahmad Aulia Jusuf (Jurnal Multidisiplin Madani, 2023)
Topical capsaicin with high concentrations (8%) is effective in the treatment of pain in Post-Herpetic Neuralgia (PHN) and HIV-Associated Distal Sensory Polyneuropathy (HIV-DSP) patients. High concentrations of capsaicin encapsulated in transfersome nanovesicles aim to reduce the irritating ability of capsaicin when using as drugs. Gel preparations were chosen in the formulation because they are non-sticky, easy to wash, easy to apply, and more practical. The components contained in the gel affect the stability of the gel. Physical and chemical stability tests need to be carried out to ensure the quality, safety and efficacy of the gel so that it meets the expected specifications during its shelf life. This study aims to determine the stability of selected gel formulas containing high concentrations of transfersome capsaicin. The selected gel formula is a gel containing a mixture of phosphatidylcholine (Phospholiphon 90G®) and Tween 80 (80:20). Stability was carried out at high temperature (40±2oC), room temperature (30±2oC), low temperature (5±3oC), and cycling test. The stability parameters tested included organoleptic, pH, viscosity, and assay. The results of the transfersom capsaicin gel stability test showed no change in pH, viscosity, and assay in all storage conditions, but the gel showed a change in color, smell, and taste when stored at high temperatures (40 ± 2oC). It can be concluded that the resulting capsaicin transfersome gel formula with a phospholipid:tween ratio of 80 (80:20) was less stable during 12 weeks of storage at 40 oC